(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Psychiatric scars from stressful events can last a lifetime and affect people who were directly or indirectly affected. Pat Barker’s book The Life Class looks at how tragedy can have a deep effect on its characters, especially on Paul, an ambulance driver who is dealing with traumatic neurosis. This paper looks at how repressed pain shows up as emotional outbursts and mental blocks, which eventually cause repressed feelings to come out and PTSD symptoms to appear. Paul’s problems show how complicated stress is and how it can have long-lasting effects on mental health. In addition, the story shows how outside triggers can bring up buried trauma, showing how damaging it is to keep feelings inside. The novel underscores the enduring scars left by tragedy, challenging conventional social norms and reshaping individuals’ perceptions of themselves and their place in the world